Production and quality of ornamental peppers cultivated under colored shade nets - Cruz, Renata Ranielly Pedroza (2023)
Temperature and intensity of solar radiation compromise the production, quality and photosynthetic efficiency, through leaf and fruit burns, photoinhibition, stomata closure, flowers and fruits abortion, among others. Colored shade nets were tested in order to identify their benefits production, quality and photosynthetic efficiency of Capsicum chinense and C. frutescens. This thesis has been divided into two papers that deal with the production and quality (paper 1), photosynthetic efficiency (paper 2) of C. chinense and C. frutescens cultivated under colored shade nets. The experiment was developed from February to August 2021 in entirely randomized design. C. chinense and C. frutescens were cultivated under red, pearl and aluminet shade nets with 35% shading and without net. At 150 days, production, quality and photosynthetic efficiency variables were quantified. The red net reduced the maximum temperature by at 4.1ºC and the pearl and aluminet nets reduced the minimum temperature by 3ºC. The maximum and minimum relative humidity was increased by 2.6 and 8.5%, respectively, by the red net. The pearl net obtained the lowest percentage of solar radiation incidence. Plant height was greater in the red and pearl nets, and C. frutescens. The diameter and stem fresh matter did not differ statistically between treatments. Root length was greater in the red and aluminet nets. The longitudinal and transverse canopy ratio was higher in C. chinense cultivated under the aluminet net. The number of leaves and leaf fresh matter was higher in pearl and aluminet net, and in C. frutescens, but leaf dry matter was higher in C. chinense. The number of flower buds and flowers, and flower buds dry matter was higher in C. chinense. The root fresh matter and dry matter was greater in C. chinese. Leaf area, leaf area duration, leaf area ratio, specific leaf area and harvest index were higher in C. frutescens in comparison to C. chinense and leaf thickness opposite occurred. A and gs were higher in C. frutescens cultivated under red net and C. chinense cultivated under aluminet net. E was higher in C. chinense cultivated under aluminet net and did not differ between the treatments applied to C. frutescens. WUE was higher in the red net and iWUE was higher in C. frutescens. Fo and Fm were higher in C. frutescens cultivated under red net. Fv/Fm was lower in C. chinense cultivated under red net and SPAD was higher in red net. LEF was lower in control. qL fraction was higher in control and pearl net and in C. frutescens. RdF was lower in C. chinense cultivated under red net. ΦNPQ and NPQt were higher in C. chinense cultivated under red net. The aluminet net in association with C. chinense are recommended considering the compactness of height, pot coverage, greater number, shape and arrangement of fruits. On the other hand, this one did not achieve efficient photosynthetic efficiency. C. frutescens cultivated under red net obtained a higher photosynthetic efficiency. On the other hand, C. chinense cultivated under red net had an inverse response, due to each specie having different responses under the same growing environment. Keywords: Shading. Productivity. Photosynthetic efficiency.